Determination of the whitten effect based on vaginal cell characteristics, vulva appearance and behavior in grouped female mice - Zakaria, Nur Hannan; Sukardi, Sabrina (Life Sciences, Medicine and Biomedicine, 2019)
Introduction: Pheromones are chemicals produced by an animal that affects the behavior of another animal or the same species. Information conveyed includes location, presence of food or threat, sexual attraction, courtship, and dam–pup interactions. Pheromones are used widely in laboratory mice facilities to synchronize estrus and simultaneous breeding for logistic purposes. Female mice housed together in the absence of the male exhibit the Lee-Boot effect of lengthened diestrus or ovarian inactive period of up to several weeks. Whitten effect is described when a large number of female mice housed together in the absence of the male and having diestrus, will enter estrous 48 to 72 hours later upon exposure to male odors or male mouse urine soaked-bedding. Objective: The aim of this study is to determine the time taken for the Whitten effect to occur based on changes in vaginal cell characteristics, vulva appearance and behavior in grouped female mice. Methodology: Ten female mice were acclimatized to the animal facility for 3 estrus cycles or 12 days. Phases of the estrus cycle were evaluated by visual observation to assess changes to the vulva and vaginal cytology. Male urine soaked-bedding were exposed to females for 3 days and the time taken for the Whitten effect to occur was determined based on changes in vaginal cell characteristics, vulva appearance and observation of behavior. Result: The Cochran’s Q test was used to observe the changes from diestrus to proestrus and later estrus. The results showed a significant difference (p<0.05) in the number of mice that successfully enter the proestrus and estrus phases over a four time point, ?2 (2) = 18.857. Conclusion: The Whitten effect occurs after 72 hours of exposure to male urine soaked-bedding based on vulva appearance, vaginal cell characteristics and behavior in grouped female mice.